2010
DOI: 10.1136/bcr.12.2009.2547
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease after vesico-vaginal stone formation around a migrated intrauterine device

Abstract: Correspondence to E B Joustra, R.Karsmakers@dz.nl SummaryAlthough the intrauterine device (IUD) seems a reliable and relatively safe method of contraception, it may cause serious complications. A rare complication is uterus perforation. Intravesical migration and secondary calculus formation is exceptionally uncommon. The authors report on a 75-year-old woman in whom a 'forgotten' migrated IUD resulted in vesico-vaginal fistula formation and chronic kidney disease, 39 years after insertion. BACKGROUND

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…A case report was found involving a migrated “Lippes Loop” with VVF, chronic kidney disease and bladder calculus. 2 We have also found two case reports of uterine perforation secondary to a “Saf-T-Coil” IUD; two of these occurred at the time of insertion, while one case presented 30 years post insertion with erosion into the peritoneal cavity and small bowel obstruction. 3 , 4 …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A case report was found involving a migrated “Lippes Loop” with VVF, chronic kidney disease and bladder calculus. 2 We have also found two case reports of uterine perforation secondary to a “Saf-T-Coil” IUD; two of these occurred at the time of insertion, while one case presented 30 years post insertion with erosion into the peritoneal cavity and small bowel obstruction. 3 , 4 …”
Section: Discussionmentioning
confidence: 92%
“…If there is intraperitoneal migration, minimally invasive or an open approach may be employed to deal with the complications as well as to remove the device, whereas in cases of intravesical migration and stone formation, cystolithotripsy of bladder calculus should be done with subsequent removal of IUD. 2 …”
Section: Discussionmentioning
confidence: 99%
“…[4] There has also been a report of intrauterine device recovered 39 years after insertion causing chronic renal disease as a result of vesicovaginal fistula formation after uterine perforation. [5] Ileal penetration has been reported as early as four weeks after insertion. [6] In an analysis of risk factors associated with uterine perforation by intrauterine devices by Caliskan et al, the risk of perforation was found to be significantly increased if the intrauterine device was inserted before 6 months of delivery.…”
Section: Discussionmentioning
confidence: 99%
“…In other case of migrating SaF-T-Coil the patient underwent cystoscopy and cystolithotripsy of a large intravesical stone. The IUD was removed via vaginal route and vesicovaginal fistula was treated [7,8].…”
Section: Discussionmentioning
confidence: 99%